2020
DOI: 10.1080/10717544.2020.1818882
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreous delivery of melatonin affects the retinal neuron survival and visual signal transmission: in vivo and ex vivo study

Abstract: Intravitreal delivery can maximize the intensity of therapeutic agents and extend their residence time within ocular tissue. Melatonin is a lipophilic molecule that crosses freely biological barriers and cell membranes. This study intends to investigate the effects of intravitreally delivered melatonin on mouse retina. The visual function of administered mice is assessed by electrophysiological and behavior examinations three weeks after intravitreal delivery. Moreover, multi-electrode array (MEA) was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 58 publications
0
6
0
1
Order By: Relevance
“…Melatonin was demonstrated to contribute beneficial effects in DR ( 16 , 18 ). As for melatonin delivery, intraperitoneal injection ( 31 ), oral administration ( 32 ), and intravitreal injection ( 33 ) were all used and tested the protective effects of melatonin on retinas in experimental animal models. In our study, considering the blood–ocular barrier and the possible side effects of systemic high-dose administration, we chose intravitreal injection to deliver melatonin directly into the eye.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melatonin was demonstrated to contribute beneficial effects in DR ( 16 , 18 ). As for melatonin delivery, intraperitoneal injection ( 31 ), oral administration ( 32 ), and intravitreal injection ( 33 ) were all used and tested the protective effects of melatonin on retinas in experimental animal models. In our study, considering the blood–ocular barrier and the possible side effects of systemic high-dose administration, we chose intravitreal injection to deliver melatonin directly into the eye.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, considering the blood–ocular barrier and the possible side effects of systemic high-dose administration, we chose intravitreal injection to deliver melatonin directly into the eye. Based on the available literature, intravitreal melatonin (50–150 μg/kg body weight) did not induce retinal morphological changes in guinea pigs ( 34 ); even the high dose from 100 to 300 µg/kg body weight did not have any significant detrimental effects on the photoreceptor survival or visual function on mouse retina ( 33 ), indicating a wide safe dose range for intravitreal injection of melatonin. In a recent study, intravitreal delivery of melatonin (150–250 μg/kg body weight) could well maintain the thickness of the outer nuclear layer in the chemical-induced retinitis pigmentosa mouse model ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Преимуществом электроретинографии является неинвазивность и простота проведения. Можно многократно прижизненно регистрировать ЭРГ у одного испытуемого животного, наблюдая эффект какого-либо воздействия в динамике сколь угодно долгое время (Tao et al 2020).…”
Section: прижизненная электроретинография как метод оценки состояния ...unclassified
“…In the current treatment of ophthalmic diseases, the ocular surface is the most common drug delivery route, and the eye drops have been widely used for delivering melatonin in animal experiments; however, their bioavailability should be further examined owing to the ocular barriers ( Dal Monte et al, 2020 ). For bypassing the barriers, the efficacy of intravitreal injection is also examined, especially in treating retinal diseases; however, the previous study reported that the high-dose melatonin injection resulted in degeneration of retinal cells ( Yilmaz et al, 2004 ; Sande et al, 2014 ; Tao et al, 2020 ). Therefore, the potential toxicity of melatonin must be further scrutinized for both the ocular surface and retina, and the proper dosages for treatment must be determined, which may be different in various ocular diseases and individuals.…”
Section: Enhancing the Bioavailabilitymentioning
confidence: 99%